VITEX NEGUNDO EXTRACTS PROTECT HUMAN CORNEAL EPITHELIAL CELLS FROM ULTRAVIOLET C-INDUCED PHOTOTOXICITY - K, DEEKSHA; ARUNACHALAM, CYNTHIA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of the study was to investigate the protective effects of Vitex negundo (VN) extracts against ultraviolet (UV) light C-induced oxidative stress in human corneal epithelial cells (HCEC) in vitro. Methods: The VN extracts were checked for their antioxidant activities by biochemical tests. The preliminary phytochemical analysis was done to check the presence of secondary metabolites. To trigger oxidative stress, the HCEC were exposed to UVC irradiation (200 J/m2). Then, different concentration of VN extracts was administered after 1 h of UVC irradiation. The effects of UVC irradiation and the extracts on the HCEC viability, morphology, cell migration by scratch assay, and reactive oxygen species (ROS) production by dichlorofluorescein diacetate method were measured. Results: VN ethanol (VNE) extract showed the highest antioxidant activity than the aqueous extract. Phytochemical screening shows the presence of alkaloids, carbohydrates, proteins, phenolics, and tannins. The extracts showed no cytotoxicity on the HCEC and also the VNE extract did not alter the morphology of the cells. Results suggest that the VNE extract enhanced the proliferation and migration of HCEC. The VNE extract significantly decreased UVC-induced oxidative toxicity by inhibiting the intracellular ROS production and maintained cell viability. Conclusion: VN extracts with its strong antioxidant potential protects HCEC from UVC-induced oxidative stress. The results suggest that these extracts can be used as prophylactic agents or as a therapeutic agent in overcoming UV light-induced damage in various ocular surface diseases such as pterygium and photokeratitis.